2008
DOI: 10.1080/02652040802354707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of morphology and drug distribution on the release process of FITC-dextran-loaded microspheres prepared with different types of PLGA

Abstract: The aim of the present work was to understand the collaborative roles and the comprehensive effects of polymer nature, morphology, drug distribution and release behaviour for PLGA microspheres prepared by the double emulsion method. The morphology and drug distribution of the FITC-dextran-loaded microspheres were investigated by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM), respectively. The results show that the morphology and release profiles depend on the polymer nature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
3
32
2
Order By: Relevance
“…For example, by increasing the porosity of the PLGA microspheres, the initial burst release of fluorescein isothiocyanate‐labeled dextran more than doubled, from 6.6% for the nonporous microspheres to 14.7% for the porous microspheres. However, the porous PLGA microspheres presented a lower release rate in the second stage; at 21 h of release, the cumulative release was around 30% for both the nonporous and porous particles . This may be due to faster neutralization of autocatalysis effect because of the presence of the pores.…”
Section: Processing Factors (Delivery System Designs)mentioning
confidence: 93%
See 1 more Smart Citation
“…For example, by increasing the porosity of the PLGA microspheres, the initial burst release of fluorescein isothiocyanate‐labeled dextran more than doubled, from 6.6% for the nonporous microspheres to 14.7% for the porous microspheres. However, the porous PLGA microspheres presented a lower release rate in the second stage; at 21 h of release, the cumulative release was around 30% for both the nonporous and porous particles . This may be due to faster neutralization of autocatalysis effect because of the presence of the pores.…”
Section: Processing Factors (Delivery System Designs)mentioning
confidence: 93%
“…It turned out that for porous microparticles, the relative lidocaine release rates were increased with decreasing particle sizes in PBS (phosphate‐buffered saline) at pH 7.4; however, for initially nonporous microparticles with identical composition, the results were exactly opposite . Porosity also affects the behavior of the initial and the second release phases from PLGA‐based systems . For example, by increasing the porosity of the PLGA microspheres, the initial burst release of fluorescein isothiocyanate‐labeled dextran more than doubled, from 6.6% for the nonporous microspheres to 14.7% for the porous microspheres.…”
Section: Processing Factors (Delivery System Designs)mentioning
confidence: 99%
“…This SR pattern was also observed in other MPs prepared with different types of PLGA polymers. 35 The terminal carboxyl group may accelerate the autocatalytic hydrolysis of the ester bonds of the biodegradable polymer and the corrosion of the MPs. Moreover, the high viscosity and boiling point of solvent (acetic acid) might influence on the compactness and/or density of MPs, minimizing burst drug release.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of PLGA MS could generate the macroporosity into the CPC through erosion and contribute to the initial strength of CPC composites in the early stages . Moreover, PLGA properties including the molecular weight and end‐group functionality could exert great influences on drug release from MS and the degradation rate of CPC composites . In our preliminary research, it have been demonstrated that SCT‐PLGA MS with 20 kDa‐COOH and 40 kDa‐COOH (SCT‐PLGA‐20 COOH MS and SCT‐PLGA‐40 COOH MS) could provide high degradation rate and sustained release of SCT, which would be beneficial for macropore formation and bone ingrowth.…”
Section: Introductionmentioning
confidence: 98%